HIV Patients' Experiences In Undergoing Anti Retroviral Therapy At Clinic 277 Advent Hospital Bandung - Fourlina Goulinq Tunjung Putih; Anita Theresia; Indra Nugraha; Wiwin Prasetyaningsih (LP3M Universitas Muhammadiyah Tasikmalaya, 2025)
Antiretroviral therapy (ARV) is an important step in improving the quality of life of HIV patients, but its implementation often presents various challenges. This study aims to understand the experiences of HIV patients undergoing ARV therapy at Clinic 277 Adventist Hospital Bandung. A qualitative approach with a descriptive phenomenological design was used to explore patient experiences in depth. Data were obtained through in-depth interviews, participant observation, and medical document analysis with the participation of six HIV patients who met the inclusion criteria. The results showed that most patients experienced deep shock and anxiety when receiving an HIV diagnosis, but social support from family, community, and health workers helped them accept the condition. During ARV therapy, the main challenges faced included physical side effects such as dizziness, nausea, and skin rashes, as well as psychological challenges in the form of social stigma. However, ARV therapy has a positive impact on physical health, psychological well-being, and social interactions of patients. Continuous education from health workers has proven important in increasing patient adherence to ARV therapy. This study recommends increasing educational programs, psychosocial support services, and public campaigns to reduce stigma against PLWHA. The implications of this research are expected to support improving the quality of health services for HIV patients in Indonesia, especially in supporting adherence to ARV therapy.